Development and Preliminary testing of a Mixing and Pelletizing Machine for Livestock Feeds Production - T.A. Ishola; R.A. Busari; O.S. Aboyeji (Journal of Applied Sciences and Environmental Management)
Agro crop residues such as cereal, stovers and fodders do not individually contain all the nutrients required for the optimum growth of ruminant animals, hence, the need to bring them together to form a balanced diet. A mixing and pelletizing machine was designed and constructed to mix and pelletize pulverized feed materials (elephant grass, wheat bran, cassava peel, molasses, cassava starch, bone meal, maize stover and groundnut cake). The mixing unit consists of the mixing hopper and a mixing chamber that houses the mixer shaft and the mixing paddles while the pelletizingunit consists of the pelletizer hopper, pelletizing barrel, a shaft with worm thread and die perforation as outlet for the pellets. A preliminary performance test was carried out on the machine to determine the effects of binder condition and moisture content on the throughput capacity and pelletizing efficiency. Three levels of binder conditions (0 kg, 0.5kg and 0.9 kg of molasses) and five levels of moisture contents (20, 22, 24, 26 and 28% (dry basis)) were used. The results showed that the highest throughput capacity and pelletizing efficiency were 116.12 kg/h and 86.76 % at a moisture content of 26 % (db) respectively. From the proximate analysis done, samples with 0.9 kg molasses generally had the highest amount of ash content, crude fibre, crude protein and crude fat. This machine would enhance the availability of nutritious pelletized feedstock for ruminant animals all year round.